UJI KONSENTRASI TIGA MACAM PUPUK ORGANIK CAIR DARI LIMBAH PERTANIAN TERHADAP - Sulistiawan Purnomo Aji; Siswadi Siswadi; Saiful Bahri (Innofarm:Jurnal Inovasi Pertanian, 2020)
This study is entitled Concentration Test of Three Liquid Organic Fertilizer From Agricultural Waste on Growth and Yield of Arugula (Eruca Sativa) to test the concentration of three kinds of liquid organic fertilizer, sugarcane bagasse waste, banana peel and coconut fiber with a concentration of 50 ml/l, 100 ml/l, and, 150 ml/l. This study uses a single Randomized Complete Design (CRD) method consisting of 10 treatments that are repeated 3 times, consisting of K0, K1, K2, K3, K4, K5, K6, K7, K8, K9, the results of this study were analyzed with Duncan's Multiple Range Test (DMRT) at 5%, the parameters observed were: plant height, number of leaves, leaf width, leaf length, root length, fresh weightof biomass, and dry weight of biomass. The results of the study show that: (1) Giving treatment (K3), liquid organic fertilizer of banana peels with a concentration of 150 ml/l, provides interaction with parameters of observation of leaf width, root length and dry weight of biomass arugula plants, but they need to increase the concentration of organic fertilizer liquid to assist the growth process with observations of plant height parameters, number of leaves, leaf length and fresh weigh of biomass. (2) Provision of treatment with 150 ml/l concentration is the best treatment for the parameters of observation of leaf width, length of root and dry weight of biomass, but the administration of 150 ml/l concentration is not sufficient for plant nutrient requirements so there is no interaction with the growth process of plant height, number of leaves, length of leaves and fresh weight of biomass. (3) The highest dry weight of biomass in the treatment of liquid organic fertilizer from banana peel waste with a concentration of 150 ml/l, weighing 4.32 g or an increase of 20% compared to the control.